2017
DOI: 10.4317/jced.54387
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpigmentation of hard palate induced by chloroquine therapy

Abstract: The antimalarials are one of the most commonly prescribed drugs for conditions such as lupus erythematosus and rheumatoid arthritis, and the side effects, though infrequent, are well known. The antimalarial agent chloroquine diphosphate usually causes pigmentary changes in the oral mucosa characterized by a bluish-grey to black discolorations mainly in the hard palate. Considering only the hard palate hyperpigmentation caused by chloroquine, to the best of our knowledge, only 13 cases have been reported in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…The literature reported that prolonged systemic administration of this drug can determine the deposition of hemosiderin in the tissues of the oral cavity. Chloroquine chelates iron and/or melanin; moreover, melanocytes are stimulated in melanin production [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…The literature reported that prolonged systemic administration of this drug can determine the deposition of hemosiderin in the tissues of the oral cavity. Chloroquine chelates iron and/or melanin; moreover, melanocytes are stimulated in melanin production [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…A detailed medical history with an accurate clinical examination is extremely important for elaboration of a diagnostic hypothesis. Due to the series of lesions presenting similar characteris-tics and yet different causes, the dentist can use an incisional biopsy for diagnostic confirmation [12] (ANDRADE et al 2017), consistently with the conduct of all authors of the studies in Table 1 [14].…”
Section: Oral Manifestationsmentioning
confidence: 96%
“…Another important aspect is managingthe use of these drugs, which needs to beperformed by the doctor (and patient) responsible for the treatment, analyzing the benefits and costs of using chloroquine and hydroxychloroquine in the medical treatment proposed. Thus, in some cases, it is possible to opt for a reduction in the usual dose or for atemporaryor definitive interruption altogether [12] (ANDRADE et al 2017). The intensity of the effects and adverse reactions will dictate such maneuvers.…”
Section: Oral Manifestationsmentioning
confidence: 99%
“…The majority of the included studies were case reports and case series, 4,5,[11][12][13][14][15][16][17][18][19][21][22][23][24][25][26][27][28][29][30][31][32][35][36][37][38][39][40][41][42][44][45][46]48,54,58,[62][63][64][65][66] most of which achieved a moderate quality level based on Murad et al's method. 9 The NOS was used for the assessment of bias in the included cohort and cross-sectional studies.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%